Pedagogical Approaches to Student-Centered Learning in Filipino Instruction: Evidence from a Rural Secondary School in Mountain Province - Caballero, Kathleen (Azal Arts and Humanities, 2026)
Student-centered learning has been widely recognized as an effective pedagogical orientation that promotes learner autonomy, engagement, and meaningful knowledge construction. However, empirical studies examining its enactment in Filipino instruction within rural secondary school contexts remain limited. This study explored the pedagogical approaches employed by a Filipino teacher in a rural public secondary school in Mountain Province and examined how student-centered learning principles were operationalized in classroom practice. Using a qualitative case study design, data were gathered through classroom observations, semi-structured interviews, and document analysis. Findings reveal that student-centered learning was enacted through contextualized instruction, dialogic teaching, collaborative activities, and inquiry-oriented tasks grounded in learners’ linguistic and cultural experiences. Despite constraints related to resources and geography, the teacher demonstrated strong pedagogical agency by adapting strategies to learners’ needs and contextual realities. The study highlights the role of teacher flexibility and reflective practice in sustaining learner-centered pedagogy in rural settings and contributes to the growing body of literature on language teaching and rural education in developing contexts.